Ostrich farmer characteristics predict conservation opportunity - Wheeler, Anita; Knight, Andrew T.; Difford, Mark; Vetter, Susanne (South African Journal of Science, 2019)
Environmental sustainability rests on human choice and action. Understanding these may assist in determining the factors that predict or influence an individual’s behaviour towards the environment. In South Africa, approximately 80% of the most threatened vegetation types are in the hands of the private agricultural community. In the Little Karoo, which is situated in the Succulent Karoo biodiversity hotspot, unsustainable land-use practices including ostrich flock breeding threaten this region’s lowland biodiversity. We interviewed ostrich farmers in the Oudtshoorn Basin to quantify latent variables thought to represent components of conservation opportunity: environmental attitude, conservation knowledge, conservation behaviour, and willingness to collaborate with agricultural, environmental and conservation organisations. Three groups of land managers were identified: (1) younger land managers (